Validitas Perangkat Pembelajaran Materi Sistem Pencernaan Manusia untuk Meningkatkan Keterampilan Berpikir Kritis Peserta Didik Jenjang SMP - Chairunisa Chairunisa; Muhammad Zaini; Rahmat Yunus (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2021)
This development research aims to evaluate the validity of learning tools for the human digestive system to improve the critical thinking skills of junior high school students. Digestive system material is studied in class VIII. This development research model uses the Tessmer Model. The research was carried out for six months (July-December 2021) at SMP Negeri 1 Martapura, Banjar Regency. The research subjects to carry out validity were three experts consisting of postgraduate lecturers at Lambung Mangkurat University. The results showed that the validity of the learning device based on the results of the expert team's validation had an average score of 75% with a fairly valid category. So the learning tools can already be used in schools after being revised, and are eligible to be continued on the individual test.